MetJ repressor interactions with DNA probed by in-cell NMR - Augustus, Anne M. (National Academy of Sciences, 2009)
Atomic level characterization of proteins and other macromolecules in the living cell is challenging. Recent advances in NMR instrumentation and methods, however, have enabled in-cell studies with prospects for multidimensional spectral characterization of individual macromolecular components. We present NMR data on the in-cell behavior of the MetJ repressor from Escherichia coli, a protein that regulates the expression of genes involved in methionine biosynthesis. NMR studies of whole cells along with corresponding studies in cell lysates and in vitro preparations of the pure protein give clear evidence for extensive nonspecific interactions with genomic DNA. These interactions can provide an efficient mechanism for searching out target sequences by reducing the dependence on 3-dimensional diffusion through the crowded cellular environment. DNA provides the track for MetJ to negotiate the obstacles inherent in cells and facilitates locating and binding specific repression sites, allowing for timely control of methionine biosynthesis.